Buddhism: a modern perspective - Prebish, Charles S.; Prebish, Charles S. (London, The Pennsylvania State University Press, 1975)
"This book is a valuable addition to the literature on Buddhism. It presents a basic and accurate survey of the tremendous variety of traditions and practices associated with Buddhism throughout the world."In the past half century Buddhist ideas have been introduced to Western countries in very impure forms due to the particular viewpoints of the adventurers and translators who interpreted them. It is especially unfortunate that Buddhism has been presented as a theistic religion, whereas in fact it is a non-theistic spiritual philosophy, psychology, and way of life. In recent decades the practice of Zen meditation has become well known in the West. While this is an improvement over the ways in which Buddhism was presented earlier, there is still very little clear presentation of other forms that meditation practice can take, or of the philosophy which is an essential part of the study of Buddhism."The value of this book, then, lies in the care and scholarship which the authors have shown in outlining the doctrines in a simple and straightforward way, and in providing ample resources for further study. It is a beginning step in the vast amount of work which needs to be done if Buddhism is to take a firm root in American soil."-Chgyam Rinpoche TrungpaThe contributors are Stefan Anacker, Stephan V. Beyer, Francis H. Cook, Roger J. Corless, Douglas D. Daye, Mark A. Ehman, Lewis R. Lancaster, and Charles S. Prebish.
Indian Buddhism -- Buddhism outside India.
Includes index.
Includes bibliographical references (pages 311-318) and index.
Keywords: Buddhism